2014
DOI: 10.1103/physrevd.90.013011
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a nondiagonal mass varying mechanism in theνμντsystem

Abstract: We use atmospheric neutrino data and MINOS data to constrain the MaVaN (Mass Varying Neutrinos) mechanism. The MaVaN model was largely studied in cosmology scenarios and comes from the coupling of the neutrinos with a neutral scalar depending on the local matter density. For atmospheric neutrinos, this new interaction affects the neutrino propagation inside the Earth, and as consequence, induces modifications in their oscillation pattern. To perform such test for a non-standard oscillation mechanism with a non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The high statistical samples of atmospheric neutrinos in the relevant energy regime made possible by these detectors, including IceCube's DeepCore, provide a rich testbed for fundamental physics and they represent a potential portal to the determination of the neutrino mass hierarchy or also ordering (NMO), to detecting sterile neutrinos and Non‐Standard Interactions, to tentatively measure the size of the CP phase in the leptonic sector (δCP) and may provide strong constraints on exotic effects like the mass varying neutrino mechanism that links the scale of baryonic matter and of the dark energy density. DeepCore has now started to constrain the atmospheric neutrino mixing parameters for the first time in the energy range that include the muon‐neutrino oscillation minimum around 25 GeV with a precision that promises to become comparable to that obtained from dedicated long‐baseline experiments using accelerators.…”
Section: Atmospheric and Cosmic Neutrinosmentioning
confidence: 99%
“…The high statistical samples of atmospheric neutrinos in the relevant energy regime made possible by these detectors, including IceCube's DeepCore, provide a rich testbed for fundamental physics and they represent a potential portal to the determination of the neutrino mass hierarchy or also ordering (NMO), to detecting sterile neutrinos and Non‐Standard Interactions, to tentatively measure the size of the CP phase in the leptonic sector (δCP) and may provide strong constraints on exotic effects like the mass varying neutrino mechanism that links the scale of baryonic matter and of the dark energy density. DeepCore has now started to constrain the atmospheric neutrino mixing parameters for the first time in the energy range that include the muon‐neutrino oscillation minimum around 25 GeV with a precision that promises to become comparable to that obtained from dedicated long‐baseline experiments using accelerators.…”
Section: Atmospheric and Cosmic Neutrinosmentioning
confidence: 99%
“…It can be shown that interactions of subgravitational force can occur naturally between ordinary matter and the field , which can cause the value of to vary from its value in vacuum [10]. This leads to neutrinos with masses dependent on the density of the medium and new effects in the flavor oscillation, motivating the study of phenomenological effects of this type of model on the Sun [11][12][13], in atmospheric neutrinos [14,15], supernovae [16,17], reactor neutrinos [18,19], and neutrinos propagating on Earth [20].…”
Section: Introductionmentioning
confidence: 99%